The Global Prevalence of Problem and Pathological Gambling and Its Associated Factors Among Individuals with Substance Use Disorders: A Meta-analysis. - Armoon, Bahram; Griffiths, Mark D.; Fleury, Marie-Josée; Mohammadi, Rasool; Bayat, Amir-Hossien (International Journal of Mental Health & Addiction, 2025)
The present systematic review and meta-analysis assessed the prevalence, sociodemographic factors, mental health disorders, and type of drug use disorders associated with problem/pathological gambling among individuals with substance use disorders (SUDs). Published studies before January 1, 2023, were reviewed. Out of 8351 papers initially identified, 61 studies remained for meta-analysis. The findings indicated that among individuals with SUDs there was a lifetime pooled prevalence rate of 23% for at-risk gambling disorder (GD), 19% for problem gambling, and 17% for pathological gambling. The pooled lifetime prevalence of SUDs among individuals with problem/pathological gambling was 18%. The findings indicated that individuals with SUDs who were male, had depressive and mood disorders, and had alcohol, tobacco, and cannabis use disorders were more likely to report problem and/or pathological gambling. Consideration of type of substance use and individuals' mental health disorders during primary treatment could be useful for reducing GD among individuals with SUDs.